The utility of TP53 and PIK3CA mutations as prognostic biomarkers in salivary adenoid cystic carcinoma. (February 2021) - Adderley, Helen; Rack, Samuel; Hapuarachi, Brindley; Feeney, Laura; Morgan, David; Hussell, Tracy; Wallace, Andrew J; Betts, Guy; Hodgson, Clare; Harrington, Kevin; Metcalf, Robert
Highlights: Largest published ACC clinical-genomics dataset. TP53-mutated ACC had significantly shorter median OS vs. TP53 wild-type ACC. Stratifying by TP53 status may usefully inform follow-up. Abstract: Objectives: Despite wide excision and post-operative irradiation, loco-regional and/or metastatic recurrence is a significant clinical problem in salivary adenoid cystic carcinoma (SACC). Reliable biomarkers are required to tailor post-treatment surveillance to patients at highest risk of recurrence. We sought to determine the utility of TP53 and PIK3CA mutations as prognostic biomarkers in SACC. Materials and methods: DNA was extracted from archival tumour blocks of 145 SACC patients from 66 UK referral centres and sequenced for TP53 and PIK3CA mutations. Clinical, pathological and outcome data were analysed to determine the impact of the genomic alterations on disease recurrence and overall survival (OS). Results: TP53 and PIK3CA mutations were identified in 8% (10/121 successful analyses) and 2% (3/121) of cases, respectively. There were too few PIK3CA mutations in this cohort for informative further analysis. TP53 -mutated SACC had significantly shorter median OS (5.3 vs. 16.3 years, p = 0.019) and lower 10-year survival (48% vs. 81%) compared with TP53 wild-type ACC. Solid-pattern histopathology was more frequent in TP53 -mutated SACC (50% vs. 15%, p = 0.27). Conclusion: TP53 -mutated recurrent and metastatic SACC was associated with shorter OS, which was significant when combined with published genomic data sets. Stratifying by TP53 status, in addition to established clinical, pathological and genomic biomarkers, may usefully inform follow-up strategy.